How Do Maternal Views of Delivery Outcomes Vary by Demographics and Preferred Mode of Delivery? - Sparks, Teresa N.; Yeaton-Massey, Amanda; Granados, Jesus M.; Handler, Stephanie J.; Meyer, Michelle; Caughey, Aaron B. (American Journal of Perinatology, 2015)
Objective To investigate how maternal views of delivery outcomes vary by demographic characteristics and preference toward mode of delivery (MOD).Study Design Survey of 719 pregnant women in outpatient clinics at an academic institution during their third trimester. Women ranked outcomes such as vaginal delivery (VD), cesarean delivery (CD), urinary incontinence, perineal lacerations, and induction of labor (IOL) on a visual analog scale (VAS) in order of worst imaginable (0) to best possible (100) outcomes.Results Women of all ages ranked VD as more desirable than CD. However, women ≥ 35 years of age had greater valuations of both MOD compared with women <35 years, with mean VAS scores of 88.4 versus 86.4 for VD (p < 0.001) and 61.5 versus 51.9 for CD (p < 0.001). Women with a college education or higher also rated both MOD as more desirable than women with less than a college education. Additionally, women who preferred VD rather than CD had greater valuations of perineal laceration (43.3 vs. 31.5, p = 0.001) and urinary incontinence (40.7 vs. 30.1, p = 0.002).Conclusion Significant differences exist in women's views toward MOD and peripartum outcomes, by demographics and preferred MOD. Understanding delivery preferences better enables clinicians to counsel women about labor and management options.
Keywords: vaginal delivery; cesarean delivery; obstetrics; maternal preferences; visual analog scale